Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Siswa Pada Tema 1 Indahnya Kebersamaaan Di Kelas IV SD Negeri 122355 Pematang Siantar - Siska Handayani Purba (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research was motivated by the low learning outcomes of students k68709IV UPTD SD Negeri 122355 Pematang Siantar. Contextual Teaching Learning (CTL) learning model on student learning outcomes in Theme 1 sub-theme 1 The Beauty of Togetherness sub-theme. The aim of this research is to determine whether or not there is an influence of the contextual teaching learning (CTL) learning model on student learning outcomes in Temq 1 Subtema 1 The Beauty of Togetherness. The approach to this research is a quantitative approach. Hypothesis test results using SPSS 21 analysis. It is known that the tcount result is 30.159. The ttable value in the statistical table with a significance of 0.05 with df n-2 is 1.68709. Because tcount (11.256) > (1.68709), the Contextual Teaching Learning (CTL) learning model influences student learning outcomes. In conclusion, regarding student learning outcomes in Theme 1 Subtheme 1 The Beauty of Togetherness.